2004
DOI: 10.1038/ni1096
|View full text |Cite
|
Sign up to set email alerts
|

T cells express a phagocyte-type NADPH oxidase that is activated after T cell receptor stimulation

Abstract: T cell receptor (TCR) stimulation induces rapid generation of reactive oxygen species, although the mechanisms for this are unclear. Here we found that T cells expressed a functional phagocyte-type nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. TCR crosslinking induced oxidase activation through the recruitment of preformed Fas ligand and Fas. TCR stimulation induced three separable events generating reactive oxygen species: rapid hydrogen peroxide production independent of Fas or NADPH oxidase; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
411
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(443 citation statements)
references
References 50 publications
28
411
1
3
Order By: Relevance
“…This was first suggested by initial observations that H 2 O 2 can mimic antigen receptor stimulation, by negatively regulating the SH2 domain-containing PTPs, SHP-1 and SHP-2 (170). Subsequent studies confirmed that T cells express essential NADPH oxidase (NOX2) components, which contribute to oxidant production and signaling upon T cell receptor (TCR) activation, thereby regulating inflammatory cytokine production and T cell adhesion (47,171). Similarly, antigen receptor stimulation in B cells has been found to involve the activation of NADPH oxidase, which serves to amplify BCR signaling by inactivation of the tyrosine phosphatase SHP-1, thereby promoting the activation of the protein tyrosine kinase Syk (170).…”
Section: Nox-mediated Signaling In Inflammatory-immune Cellsmentioning
confidence: 96%
“…This was first suggested by initial observations that H 2 O 2 can mimic antigen receptor stimulation, by negatively regulating the SH2 domain-containing PTPs, SHP-1 and SHP-2 (170). Subsequent studies confirmed that T cells express essential NADPH oxidase (NOX2) components, which contribute to oxidant production and signaling upon T cell receptor (TCR) activation, thereby regulating inflammatory cytokine production and T cell adhesion (47,171). Similarly, antigen receptor stimulation in B cells has been found to involve the activation of NADPH oxidase, which serves to amplify BCR signaling by inactivation of the tyrosine phosphatase SHP-1, thereby promoting the activation of the protein tyrosine kinase Syk (170).…”
Section: Nox-mediated Signaling In Inflammatory-immune Cellsmentioning
confidence: 96%
“…An intact Txn system may be necessary to attenuate signaling by surface receptors. In response to ligand binding, NADPH-oxidase enzymes associated with the cytosolic aspect of growth factor receptors generate H 2 O 2 [22][23][24]26,[75][76][77][78][79][80][81][82][83]. A conserved catalytic cysteine at the active site of protein tyrosine phosphatases is oxidized by H 2 O 2 to a sulfenic acid, which further reacts with a backbone nitrogen to form a sulfenylamide [68].…”
Section: Effects On Signalingmentioning
confidence: 99%
“…In addition to its general roles, Txnrd1-dependent reduction reactions are important in specific cells or situations for limiting signal transduction from several cell surface receptors, including the T cell receptor, the insulin receptor, and the epidermal growth factor receptor [21][22][23][24][25][26][27]. Txn1 is also required for DNA-binding activity of the transcription factors NFκB, AP1, steroid hormone receptors, and p53 [1,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This result was consistent with an earlier report that PHA and PMA induce oxidative product formation in the Jurkat malignant T cell line (12). Although the intracellular source of ROI production in T cells is still being investigated, studies have implicated the mitochondria as well as a phagocyte-type NADPH oxidase as contributors (13)(14)(15)(16)). An essential role for ROI in T cell function was initially demonstrated by reports indicating that antioxidants inhibit proliferation and IL-2 production when administered during the early stages of T cell activation (17,18).…”
mentioning
confidence: 99%